Telaah filosofis tentang keadilan kontributif dan Martabat kerja manusia serta implikasinya bagi Paradigma ekonomi - Petrus Tan; Yolinda Yanti Sonbay; Beatrix Yunarti Manehat (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
Abstract This article aims to present the limitations of distributive justice theory as a conceptual foundation of the paradigm of the growth and prosperity in economy, and then proposing the idea of contributive justice and the dignity of human work as a new economic paradigm. Why is contributive justice important, and what is its relevance in the discourse of economic paradigm? By using the method of literature study and critical analysis, this article indicates that the idea of contributive justice is essential to overcome the lack of distributive justice. The distributive justice fails to understand that human labour is not only economic. Human labor is not just an instrument for consumption purpose. Human labour is essentially social and cultural. Based on the very idea of contributive justice, human labour is a source of individual self-social esteem, the way of contributing for common good and winning the social recognition from the society. Amid the global economic competition that intensifies the social and economic inequality, contributive justice offers the idea of dignity of human work as a new paradigm of economy. This article concludes that economic efforts in the 21st century, both in the global and in Indonesia, must considerthe dignity and value of human work.Key Words : Distributive justice; contributive justice; economy; the dignity of human work.